Episodes of status epilepticus in young adults: Etiologic factors, subtypes, and outcomes - MİDİ, İPEK; AĞAN YILDIRIM, KADRİYE (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2013)
The aim of this study was to evaluate the type, duration, etiology, treatment, and outcome of status epilepticus (SE) episodes, among patients aged 16-50 years. A total of 101 SE episodes in 88 young adult patients fulfilled our criteria. The mean age was 32 years. Status epilepticus episodes were most frequently observed in patients 21-30 years of age. A total of 53% of the patients were male, and 57% had pre-existing epilepsy. Seventy of the 101 episodes were convulsive SE. The most common etiology was withdrawal of or change in antiepileptic drugs (AEDs), seen in 31% of the SE episodes. This study included treatment of SE with traditional AEDs. Sixty-six episodes were treated successfully with intravenous infusion of 18-mg/kg phenytoin, and six episodes were treated with 10-mg/kg phenytoin. A total of 28% of the SE episodes remained refractory to first-line treatment, which was related to the duration of SE and mortality. The outcome was death in 14% of the patients due to underlying etiologies in the hospital. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Status epilepticus; Etiology; Treatment and outcome; Young adult; CONVULSIVE STATUS EPILEPTICUS; REFRACTORY STATUS EPILEPTICUS; PREDICTORS; PROGNOSIS; EPIDEMIOLOGY; MORTALITY; CHILDREN; DEATH